Platelet-to-Albumin Ratio: A Novel IgA Nephropathy Prognosis Predictor - Tan, Jiaxing; Song, Guojiao; Wang, Siqing; Dong, Lingqiu; Liu, Xiang; Jiang, Zheng; Qin, Aiya; Tang, Yi; Qin, Wei (Frontiers in Immunology, 2022)
Background: Chronic inflammation is related to the development of IgA nephropathy (IgAN). Emerging studies have reported that platelet-related parameters including platelet (PLT), platelet-to-albumin ratio (PAR) and platelet-to-lymphocyte ratio (PLR), are proved to be novel prognostic indicators for several inflammatory diseases. Whether platelet-related parameters could serve as predictors for IgAN remains unknown. Methods: A total of 966 IgAN patients were finally enrolled in this retrospective study and were divided into several groups based on the optimal cut-off value of the platelet-related parameters. End-stage renal disease was used as the renal endpoint. A 1:2 propensity score (PS) match was then carried out to eliminate significant differences at baseline. The area under the receiver operating characteristic curve (AUROC), Kaplan–Meier (K-M) curve and Cox proportional hazards analyses were performed to evaluate their predictive effect. Results: Without considering the effect of covariates, the K-M curve showed that PLT, PLR and PAR were strongly correlated with the renal outcomes of IgAN. However, the AUROC revealed that the PAR and PLR had better predictive power than the PLT. Multivariate Cox regression adjusting for demographic data, pathological findings, treatment and laboratory results indicated that compared with PLR, albumin and PLT, PAR seemed to be a better marker of adverse renal outcome, implying that PAR was the only platelet-related parameter that could be used as an independent risk factor. Notably, high PAR patients seemed to have more severe clinical manifestations and pathological lesions. However, after eliminating the influence of different baselines on outcome variables, the PAR could still predict the poor prognosis of IgAN. To more accurately evaluate the predictive power of the PAR, we analyzed the predictive effect of the PAR on patients with different clinicopathological characteristics through subgroup analysis. It was indicated that the PAR might better predict the prognosis and outcome of patients who were already very severe. Conclusion: PAR might be used as an independent risk factor for IgAN progression.